Accelerators in Silicon Valley : Building Successful Startups - Ester, P. (Book collections on Project MUSE., 2019)
Silicon Valley is the world's most successful innovation region. Apple, Google, Facebook, Instagram, Twitter, WhatsApp, Uber, and Airbnb changed our way of living. Silicon Valley has built a brilliant ecosystem that supports startups. Its entrepreneurial mindset fosters risk-taking, thinking big, and sharing. A fast growing number of accelerators in Silicon Valley help startups by bringing their product to the market, refining their business idea, developing their product, strengthening their team, designing a marketing strategy, getting first customers and traction, raising funds, and coping with the hardships of startup life. In Accelerators in Silicon Valley Peter Ester describes how these 'schools of startup entrepreneurship' operate and empower startups. What can we learn from how Silicon Valley accelerators help startups to become successful companies? This book gives the answer. Accelerators in Silicon Valley is a book for those who share a fascination for building the new startup economy.